Framing the future of the COVID-19 response operations in 2022 in the WHO African region - Thierno Balde; Boniface Oyugi; Humphrey Karamagi; Joseph Chukwudi Okeibunor; Ishata Nannie Conteh; Nonso Ephraim Ejiofor; Phionah Atuhebwe; Miriam Nanyunja; Amadou Bailo Diallo; Richard Mihigo; Zabulon Yoti; Fiona Braka; et al. (Taylor & Francis Group, 2022)
Background With the evolving epidemiological parameters of COVID-19 in Africa, the response actions and lessons learnt during the pandemic's past two years, SARS-COV 2 will certainly continue to circulate in African countries in 2022 and beyond. As countries in the African continent need to be more prepared and plan to 'live with the virus' for the upcoming two years and after and at the same time mitigate risks by protecting the future most vulnerable and those responsible for maintaining essential services, WHO AFRO is anticipating four interim scenarios of the evolution of the pandemic in 2022 and beyond in the region. Objective In preparation for the rollout of response actions given the predicted scenarios, WHO AFRO has identified ten strategic orientations and areas of focus for supporting member states and partners in responding to the COVID-19 pandemic in Africa in 2022 and beyond. Methods WHO analysed trends of the transmissions since the first case in the African continent and reviewed lessons learnt over the past months. Results Establishing a core and agile team solely dedicated to the COVID-19 response at the WHO AFRO, the emergency hubs, and WCOs will improve the effectiveness of the response and address identified challenges. The team will collaborate with the various clusters of the regional office, and other units and subunits in the WCOs supported with good epidemics intelligence. COVID-19 pandemic has afflicted global humanity at unprecedented levels. Conclusion Two years later and while starting the third year of the COVID-19 response, we now need to change and adapt our strategies, tools and approaches in responding timely and effectively to the pandemic in Africa and save more lives.